Autoconcepto Físico, Personal, Social Y Académico En Adolescentes Chihuahuenses - Perla Jannet Jurado García; Susana Ivonne Aguirre Vásquez; Miguel Conchas Ramírez; Fernando Mondaca Fernández; Raúl Josué Nájera Longoria; José René Blanco Ornelas (European Scientific Journal, ESJ, 2018)
The aim of this study consisted in determining the differences and similarities among Mexican high school students concerning their selfconcept. A total sample of 544 participants, 264 women and 280 men, with a mean age of 12.96 years (DS= 0.94) and 12.85 years (DS= 0.98) respectively. A quantitative approach with a descriptive and transversal survey design was used. All the participants completed the Self-concept Questionnaire AUDIM of Rodríguez and Fernández (2011). The results of the one-way multivariate analysis of variance, followed by the one-way univariate analyses of variance, showed that compared with the women, the men obtained higher scores on the subscales Physical Self-concept, Social Self-concept and General Selfconcept. However, in Academic and Personal Self-concept subscales statistically significant differences were not found. Further research should reply these findings in larger samples.